Konsep Etika Sosial dalam Pandangan Ketuhanan Jean-Luc Marion di Era Postmodern - Rudolfo Jacob Manusiwa; Irene Ludji; Izak Y. M. Lattu (Studia Philosophica et Theologica, 2023)
This research delves explicitly into and elaborates on the concept of social ethics through the eyes of Jean-Luc Marion's concept of divinity. Through this research, the author understood the contribution of Marion's theory regarding the human face as an icon in social lives during the postmodern era. In order to get the results from the research, a qualitative approach to the literature study was used. The results show that Marion's ideas complete the concept of social ethics characteristics, which can formulate ethics. Marion offers to live icon relations and reject idol relations in social lives because icon relations are relevant for eliminating truth claims (God) within the framework of displaying the character of religious adherents that are inclusive, hospitable, and constructive actions appreciative of each of the characteristics of the various definitions and concepts of divinity. Icon relations live the values of inclusiveness, accepting and being open to plural truth (definition and concept of God), and viewing truth as relative. Furthermore, Marion's understanding of human relations with humans speaks phenomenologically and is normative. Human relations refer to individual awareness that the responses in living together are ethical orders that speak through faces (icon), and the context of agape is also present. Ethical orders and agape will always burden the individual when every time he is faced with the face (icon) of another being.